Eupeodes luniger (Diptera, Syrphidae) a new record to Greece and a key for the genus Eupeodes in this country - Perez-Banon, C.; Marcos-Garcia Μ.-Α.; Petanidou Τ. (ENTOMOLOGIA HELLENICA, 2000)
Eupeodes luniger (Meigen, 1822) (Diptera, Syrphidae), an aphidophagous hoverfly species that acts also as pollinator, was recorded for the first time in Greece. Based on the Greek records, we provide the first identification key for the genus Eupeodes Osten Sacken, 1877 in Greece.